2017
DOI: 10.1136/bcr-2016-218589
|View full text |Cite
|
Sign up to set email alerts
|

Topical timolol for the treatment of pyoderma gangrenosum

Abstract: Treatment of pyoderma gangrenosum (PG) remains a challenge, and there are currently no specific or uniformly effective therapies. Although widespread or rapidly progressive disease often requires systemic treatment, localised and mild lesions may be effectively controlled with topical agents. The most frequently applied topical drugs are corticosteroids and calcineurin inhibitors. Recently, a patient with idiopathic PG of the lower limb was successfully treated with topical timolol and collagenase. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In a double-blind randomized controlled trial, patients who received oral propranolol had a shorter time to healing of superficial wounds and were quicker to receive skin grafts in deeper injuries 5 . Also, topical beta-blocker timolol was shown to promote healing of chronic wounds of various causes 6, 7, 8. Oberbeck et al 9 explained the immunomodulatory effects of topical timolol.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind randomized controlled trial, patients who received oral propranolol had a shorter time to healing of superficial wounds and were quicker to receive skin grafts in deeper injuries 5 . Also, topical beta-blocker timolol was shown to promote healing of chronic wounds of various causes 6, 7, 8. Oberbeck et al 9 explained the immunomodulatory effects of topical timolol.…”
Section: Discussionmentioning
confidence: 99%
“…From this wound‐healing standpoint, the effects of topical timolol on acute surgical wounds have been tested in six patients, demonstrating that topical timolol application could improve the overall cosmesis of acute surgical wounds, decreasing vascularity compared to control. 43 …”
Section: Other Uses Of Topical Beta‐blockersmentioning
confidence: 99%
“…Several animal studies have indicated that administration of b-blockers improves cutaneous and burn wound healing. 77,78 The increased re-epithelialization speed may be explained by the enhanced keratinocyte migration via b-blockage. [68][69][70][71][72][73][74] Furthermore, two randomized controlled trials including 79 and 69 burn patients found that oral propranolol administration markedly decreases the time needed to receive skin graft and the area needed to be grafted.…”
Section: Wound Healingmentioning
confidence: 99%
“…Two case studies found topical timolol to be effective in treating ulcerated skin lesions which eventually lead to complete re-epithelialization. 77,78 The increased re-epithelialization speed may be explained by the enhanced keratinocyte migration via b-blockage.…”
Section: Wound Healingmentioning
confidence: 99%